Role of non-government organizations in engaging medical students in research. (1st February 2017) - Manoranjan, Branavan; Dey, Ayan K; Wang, Xin; Kuzyk, Alexandra; Petticrew, Karen; Carruthers, Chris; Arnold, Ian
Abstract : The continued decline in medical trainees entering the workforce as clinician-scientists has elevated the need to engage medical students in research. While past studies have shown early exposure to generate interest among medical students for research and academic careers, financial constraints have limited the number of such formal research training programs. In light of recent government budget cuts to support research training for medical students, non-government organizations (NGOs) may play a progressively larger role in supporting the development of clinician-scientists. Since 2005, the Mach-Gaensslen Foundation has sponsored 621 Canadian medical student research projects, which represents the largest longitudinal data set of Canadian medical students engaged in research. We present the results of the pre- and post-research studentship questionnaires, program evaluation survey and the 5-year and 10-year follow-up questionnaires of past recipients. This paper provides insight into the role of NGOs as stakeholders in the training of clinician-scientists and evaluates the impact of such programs on the attitudes and career trajectory of medical students. While the problem of too few physicians entering academic and research-oriented careers continues to grow, alternative-funding strategies from NGOs may prove to be an effective approach in developing and maintaining medical student interest in research.